Biosolids Engineering and Management - Wang, Lawrence K.; Shammas, Nazih K.; Hung, Yung-Tse (Handbook of Environmental Engineering, 2008)
Over the last 30 years, pollution and its effects on the environment have emerged as leading topics of interest. The desire for positive action to restore and protect the environment is growing worldwide. How serious are particular types of pollution? Is technology currently available to abate pollution? And do the costs of abatement justify the degree of abatement achieved? In the series, Handbook of Environmental Engineering, these questions are answered for the three basic forms of pollution and waste: gas, solid and liquid. Volume 7 in the series, Biosolids Engineering and Management, is a collection of methods of practical design, calculation and numerical examples that illustrate how organized, analytical reasoning can lead to the discovery of clear, direct solutions, especially in the areas of biosolids management, treatment, disposal and beneficial use. The book's distinguished panel of authors provides insight into a range of topics, including sludge and biosolids transport, pumping and storage, sludge conversion to biosolids, chlorination, stabilization, regulatory requirements, costs, agricultural land application, landfill, ocean disposal, combustion, incineration and sludge treatment process selection. Along with its sister book - Volume 6, Biosolids Treatment Processes - Volume 7 is designed to be a basic biosolids treatment textbook, as well as a comprehensive reference book for advanced undergraduate and graduate students, designers of waste treatment systems, scientists and researchers. Both insightful and illuminating, Volume 7, Biosolids Engineering and Management gives state-of-the-art illustrations of the theory and practice of individual biosolids management systems and pertinent information on physical, chemical and biological treatment technologies used today.